A Survey of Teachers' Beliefs about English Teaching and Learning - Meilani, Rini Intansari (2007)
The purpose of this study is to get insight into teachers' beliefs about English teaching and learning. Involving forty-two Junior High School English teachers in Sukabumi, this study uses data gained from an open-ended cross-sectional survey questionnaire. The data were analyzed both qualitatively and quantitatively. The results of the analyses revealed that the teachers in this study believe that English teaching and learning is a professional activity for attaining real life purposes. They believe that these purposes can be achieved by way of teaching all the macro linguistic skills effectively by using certain criteria of good practices, which are consistent with professional knowledge and competence, by using appropriate teaching guidelines and sources for the purposes of facilitating and motivating students' optimal learning to get good scores. Believing it as a professional activity, the teachers think that their job requires continuous improvement and evaluation to ensure personal development and prozessional benefit. This study supports the idea that teachers' beliefs play a great impact on almost every professional decision making the teachers make throughout their professional lives. A set of recommendations that give future directions for further research and teachers' professional development are presented.